Perencanaan Perawatan Mesin Dengan Metode Reliability Centered Maintenance II Di PT Naga Laut Timur - Ahmad Amirudin; Ari Zaqi Al Faritzy (Pusat Riset dan Inovasi Nasional, 2023)
PT Naga Laut Timur is a company engaged in the fish freezing industry. In carrying out its production process, this company is assisted by 2 types of machines, namely compressor machines and cold storage machines. After several years of the production process, the condition of the cold storage machines began to experience a lot of damage and downtime often occurred. Where in February 2022 - January 2023 the frequency of damage to cold storage machines reached 48 times and machine downtime reached 582.5 hours. Efforts made to improve that is by using the RCM II method. From the FMEA calculation results, three critical components have the highest RPN values, namely the Solenoid Valve, Shut Off Valve and Filter Drier Components. Optimal maintenance interval on Solenoid Valve with a maintenance interval of 279.2925 hours. Shut Off Valve with optimal maintenance interval of 331.3482 hours. Filter Drier with optimal maintenance interval of 345.3584 hours. The maintenance action on the Solenoid Valve uses a scheduled on-condition task with an optimal TC of IDR 4,334,846. Shut Off Valve uses a scheduled on-condition task with an optimal TC of IDR 5,859,706. Filter Drier uses the Sheduled Discard Task with an optimal TC of IDR 3,919,122.